2020
DOI: 10.1088/2057-1976/ab6ed1
|View full text |Cite
|
Sign up to set email alerts
|

An artifact-free thyroid shield in CT examination: a phantom study

Abstract: This study was to evaluate dose reduction and resulting image quality of a new synthetic thyroid shield based on silicon rubber (SR)-lead (Pb) composites and compare to tungsten paper (WP) and a Radibabarrier thyroid shields in CT examination of the neck. The synthetic SR-Pb thyroid shield had a Pb percentage from 0 to 5 wt% and a thickness of 0.6 cm. Scanning on the neck of an anthropomorphic phantom was performed with and without the SR-Pb, WP, and Radibarrier thyroid shields. The thyroid shields were placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Our results showed that Saba shield and 100% Bi shield with thickness of 1T reduced the surface dose down to 50.2% and 51.7%, respectively. Radiation dose saving by our constructed shields is more than the reported values by Hohl et al [21], Inkoom et al [22], Lambert and Gould [23], Catuzzo et al [24], Sutanto et al [25] and Santos et al [26]. Hoang et al showed that O-TCM, and O-TCM with bismuth shield reduced thyroid dose down to 28% and 45%, respectively [20].…”
Section: Dose Reductionmentioning
confidence: 54%
“…Our results showed that Saba shield and 100% Bi shield with thickness of 1T reduced the surface dose down to 50.2% and 51.7%, respectively. Radiation dose saving by our constructed shields is more than the reported values by Hohl et al [21], Inkoom et al [22], Lambert and Gould [23], Catuzzo et al [24], Sutanto et al [25] and Santos et al [26]. Hoang et al showed that O-TCM, and O-TCM with bismuth shield reduced thyroid dose down to 28% and 45%, respectively [20].…”
Section: Dose Reductionmentioning
confidence: 54%
“…According to the International Commission on Radiological Protection (ICRP), the breast is one of the most vulnerable human organs to radiation and must be protected. The breast tissue weight factor is 0.12, meaning that the detriment from stochastic effects resulting from irradiation of that tissue compared to uniform whole-body irradiation is about 12% [4][5][6][7][8]. Therefore, the "as low as reasonably achievable (ALARA)" principle should be used to optimize the radiation dose [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Hence there is a need for an alternative shielding material that is able to reduce the dose while maintaining image quality. Alternative materials of SR-Pb for dose reduction in specific organs, such as the thyroid, eyes, and gonads, have been reported [8,24,25]. It was found that SR-Pb reduces dose while maintaining image quality [8,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the resulted image quality has not been discussed in the report [ 12 ]. Another alternative material for organ shield from SR-Pb has been reported [ 13 - 15 ]. Previously, the small percentage of Pb from 1-5 wt% in the SR-Pb has been used for reducing eye dose in the head CT examination [ 14 ].…”
Section: Introductionmentioning
confidence: 99%